Meningkatkan Hasil Belajar Pakat dengan Model PBL pada Materi Sepuluh Perintah Allah Kelas IV SD Santa Veronika Pekanbaru - Herlindawati Herlindawati (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to examine the improvement of cognitive and affective learning outcomes in the creative dimension through the Problem-Based Learning (PBL) model among students at Santa Veronika Elementary School in Pekanbaru. The research is based on the issue of students' diverse religious backgrounds, which makes it difficult for them to understand the context and relevance of the Ten Commandments in everyday life. Additionally, the monotonous teaching methods contribute to low interest and poor learning outcomes. There is also a need to enhance students' social skills and piety towards God within the context of Catholic Religious Education (PAK) and character development. This research is a classroom action research consisting of four steps: planning, implementation, observation, and reflection in each cycle. The study was conducted over two cycles at Santa Veronika Elementary School in Pekanbaru, with fourth-grade students learning about the Ten Commandments as a guide for life. The study took place in September 2024. Data collection techniques included learning outcome tests and affective observation rubrics that assess the dimensions of faith, piety towards God, noble character, and teamwork. The data analysis was conducted using quantitative descriptive techniques. The results of the first cycle showed an improvement in students' learning outcomes and involvement, but the target was not fully achieved. In the second cycle, there was a significant increase in both learning outcomes and students' affective engagement. The study demonstrated a 30% increase in learning outcomes and student participation in PAK lessons. This research is expected to provide solutions to the low learning outcomes in Catholic Religious Education, particularly in the subject of the Ten Commandments for fourth-grade students at Santa Veronika Elementary School in Pekanbaru.